Luminescence regulation of Sb3+ in 0D hybrid metal halides by hydrogen bond network for optical anti-counterfeiting - Dehai Liang; Saif M. H. Qaid; Xin Yang; Shuangyi Zhao; Binbin Luo; Wensi Cai; Qingkai Qian; Zhigang Zang (Opto-Electronic Advances, 2024)
The Sb3+ doping strategy has been proven to be an effective way to regulate the band gap and improve the photophysical properties of organic-inorganic hybrid metal halides (OIHMHs). However, the emission of Sb3+ ions in OIHMHs is primarily confined to the low energy region, resulting in yellow or red emissions. To date, there are few reports about green emission of Sb3+-doped OIHMHs. Here, we present a novel approach for regulating the luminescence of Sb3+ ions in 0D C10H22N6InCl7·H2O via hydrogen bond network, in which water molecules act as agents for hydrogen bonding. Sb3+-doped C10H22N6InCl7·H2O shows a broadband green emission peaking at 540 nm and a high photoluminescence quantum yield (PLQY) of 80%. It is found that the intense green emission stems from the radiative recombination of the self-trapped excitons (STEs). Upon removal of water molecules with heat, C10H22N6In1-xSbxCl7 generates yellow emission, attributed to the breaking of the hydrogen bond network and large structural distortions of excited state. Once water molecules are adsorbed by C10H22N6In1-xSbxCl7, it can subsequently emit green light. This water-induced reversible emission switching is successfully used for optical security and information encryption. Our findings expand the understanding of how the local coordination structure influences the photophysical mechanism in Sb3+-doped metal halides and provide a novel method to control the STEs emission.